Poleward migration of western North Pacific tropical cyclones driven by genesis location shift under global warming in HighResMIP-PRIMAVERA models - Mingyu Li; Chaoxia Yuan; Jiuwei Zhao; Qingqing Li (npj Climate and Atmospheric Science)
Abstract The latitudinal position of lifetime maximum intensity ( $${φ }_{LMI}$$ φ LMI ) of tropical cyclones (TCs) in the western North Pacific (WNP) has been observed to migrate poleward over the last several decades, but the cause remains not fully understood. In this study, we utilized 20 models from the PRIMAVERA project with different configurations to investigate long-term changes in the $${φ }_{LMI}$$ φ LMI in the WNP. Over a hundred-year simulations under global warming, most models demonstrate a poleward shift of $${φ }_{LMI}$$ φ LMI with a multi-model-mean rate of 0.068° decade−1. This poleward trend can be predominantly explained by the poleward shift of TC genesis latitude. Specifically, the poleward shift of TC genesis latitude contributes 0.28° decade−1 to the trend, the meridional shift of the Hadley circulation’s ascending branch contributes 0.03° decade−1, but they are largely offset by the negative contribution of -0.24° decade−1 by the decreasing lifetime maximum intensity.